Path and Practice of Gap Management in National Parks: A Comparison Between China and the US and Inspirations Therefrom - Yun MA; Siyuan HE (Fengjing Yuanlin)
ObjectiveThis research examines the concept and management practices of “gap” (also known as “sky window”) in national parks, focusing on China and the US. These gaps are areas that are temporarily “drawn out” or excluded from the boundary of protected areas to resolve conflicts between ecological protection and the development needs of local communities. While China has adopted a top-down approach to “open gaps” in national parks as part of its protected area system reform, the US federal land system offers insights into the management of similar gaps through tools like land acquisition and conservation easement. This research aims to explore the institutional motivations, potential challenges, and optimization paths of the spatial planning concept of “gap”, focusing on how these gaps impact the effectiveness of protection and regional development. Through a comparative approach, the research identifies key institutional factors shaping the management of these gaps and provides recommendations for improving China’s approach to gap management.MethodsThis research employs a combination of policy text analysis, historical analysis and comparative analysis to explore the concept and management of “gap” in national parks in both China and the US. By reviewing policy documents and examining historical developments, this research traces the evolution of the “gap” concept in both countries, and compares their respective institutional frameworks, management systems, and strategies for addressing these gaps. The research highlights key similarities and differences between the two countries in the aforesaid aspects, and proposes policy recommendations for optimizing gap management in China’s national parks.ResultsIn China, the concept of “gap” in land planning generally refers to small areas within designated zones that do not align with the intended function, such as plots scattering in ecological protection, agricultural, and urban development zones. The practice of “gap opening” allows for flexibility in land use, enabling the inclusion or exclusion of land parcels that undertake agricultural, ecological, and urban functions within certain zoning boundaries. However, this approach raises concerns about ecological integrity, particularly when it leads to fragmentation, reduced connectivity, and potential ecological risks. In national parks, “gap community” refers to human settlements within or adjacent to protected areas, which present significant management challenges. These communities often pose threats to ecological integrity due to urban infrastructure and intensive resource use. Despite efforts to integrate these areas into a unified management framework, these communities are primarily controlled by local governments, with limited support from the competent park authorities. This separation from national park management has hindered the sustainable development of these communities and undermined broader conservation goals. The complexity of managing these “gap” areas highlights the need for more adaptive and integrated management strategies that balance conservation and community needs. In the US, the management of “gap” in federal lands is in alignment with the evolution of historical land policies, which gives birth to “inholding” — non-federal lands surrounded by federally owned territories. These gaps, akin to China’s “gap” concept, present challenges due to differences in land ownership and management goals. As inholdings often originate from land transfers during the territorial expansion of the US, they create fragmented ownership patterns, complicating federal land management. The management of inholdings remains decentralized, with varied legal frameworks depending on local government policies. These gaps disrupt ecosystem continuity, raise management costs, and increase conflicts between private landowners, federal agencies, and the public. Conflicting interests between federal conservation goals and local economic incentives exacerbate the issue. To address these challenges, two institutional approaches are identified: Top-down federal control, such as land acquisition, and bottom-up local regulation. However, the two approaches both face legal and fiscal constraints, including political resistance, legal uncertainty, and limited funding. The “Cod Cape Model” represents a compromise, blending federal authority with local regulator for gap management, allowing for flexible governance and local compliance with federal objectives. This model has been adopted by several parks, balancing top-down and bottom-up governance. In summary, both China and the US face similar challenges in gap management within national parks, primarily related to land ownership disparities, diverse land functions, and the complex coordination of multiple interests. However, the approaches adopted by the two countries differ significantly. In China, the concept of “gap opening” is dynamic and proactive, focusing on land use and future spatial planning, often separating human activity from nature. This approach may lead to park “isolation” and complicate integrated management. In contrast, the US predominantly employs a “gap closing” strategy, seeking to resolve the issues of land ownership and functional discrepancy through legal tools and land regulation. Although both countries aim to balance ecological protection, economic growth, and social equity, the US faces challenges with fragmented land ownership, while China contends with conflicts between resource use and community development within park boundaries.ConclusionThe establishment and management of “gap” are critical for achieving the effective protection of national parks and the coordination of regional development. China’s national park planning should reflect on the legitimacy of “gap” and develop a legitimacy evaluation system for human activities, while transiting from merely opening gaps to managing them through classified control and spatial coordination. Additionally, China may learn from the institutional tools used in the US for managing gaps on federal lands, and select and combine these tools to increase the efficiency and effectiveness of national park protection.